Crypt of the ancient Nunnery of St. Helen, Bishopsgate Street - Wise, William; Capon, William (Tufts Archival Research Center, 2008)
Over which was erected the Hall of the Leathersellers Company. Taken in 1799. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.